Otimização de uma formulação de fishburger de jundiá (Rhamdia quelen) visando o aproveitamento de resíduos da filetagem do processamento de frutas - Bochi, Vivian Caetano (2007)
This work was aimed at optimizing a formulation of silver catfish fishburgers (Rhamdia quelen) using filleting wastes and extract from fruit seeds. The utilization of filleting wastes from silver catfish in the formulation of fishburgers was evaluated by replacing grounded fish fillets with increasing levels (0-control, 20, 50, and 80%) of pulp obtained from filleting wastes (PFW). Fat content of burgers increased with increasing levels of PFW (p<0.05). Burgers with 50-80% PFW had lower n-6/n-3 ratio than control (p<0.05). Fat and moisture retention after cooking were not affected by PFW, while cooking yield increased in burgers with 50% PFW when compared to all other formulations (p<0.05). Texture and juiciness were not affected by PFW. However, burgers containing 80% PFW had lower overall acceptance than controls (p<0.05). Mango (Mangifera indica L.), peach (Prunus persica), and passion fruit (Passiflora sp.) seeds were examined for their total phenolic content, radical scavenging capacity against DPPH (1,1-diphenyl-2-picrylhydrazyl) radicals, ferric-reducing antioxidant power (FRAP), and antioxidant activity against lipid oxidation in a fish model system (0.05, 0.1, 0.15, and 0.3 mg phenolic compounds/4.4ml of silver catfish homogenate). Mango seed extract (MSE) showed the highest phenolic content and total antioxidant activity by DPPH and FRAP assays. Lipid oxidation in fish model system (at 37oC during 90 min) was retarded by the three seed extracts at all concentrations tested. MSE that had the highest antioxidant activity in vitro, was also evaluated against lipid oxidation in fishburgers produced from silver catfish filleting wastes. Burger formulations with 50% pulp from filleting wastes were prepared containing MSE (0, 30, and 90 ppm phenolic compounds) and conjugated dienes, peroxide value, tiobarbituric acid reactive substances, and free fatty acids were the oxidation products measured during frozen storage at -10 and -20oC. All lipid damage measurements were affected by the storage time and temperature. However, after 120 days at both temperatures, TBARS levels of fishburgers did not reach threshold limit for human consumption. MSE had no antioxidant effect against lipid oxidation in silver catfish burgers. Filleting wastes could substitute up to 50% of fish fillets with no changes in sensory acceptance, an improvement of nutritional value, and cooking characteristics, with good lipid stability during at least 120 days of freezing storage.